Impact of COVID-19 on tuberculosis detection and treatment in Baja California, México - Muñiz-Salazar, Raquel; Le, Tina; Cuevas-Mota, Jazmine; González-Fagoaga, Jesús Eduardo; Zapata-Garibay, Rogelio; Ruiz-Tamayo, Paola Saritzia; Robles-Flores, Javier; Garfein, Richard S. (Frontiers in Public Health, 2022)
In 2020, Mexico reported the lowest tuberculosis (TB) incidence on record, and it is unclear to what extent COVID-19 has impacted TB surveillance, diagnosis, and treatment. It is important to understand COVID-19's impact in Baja California (BC), which has the highest TB burden in Mexico. With the increasing number of migrants and asylum seekers arriving in BC, limited resources and crowded living conditions increase the risk of TB transmission. The purpose of this study was to assess the impact of COVID-19 on TB diagnosis and treatment in BC. We were also interested in health disparities experienced by migrants in BC. We conducted a mixed methods analysis using quantitative surveillance data obtained from the Mexico National TB Program (NTP) and qualitative data collected through in-depth interviews and focus group discussions with TB program directors and personnel in BC's four provincial health jurisdictions. Compared to the year prior, surveillance data from March 2020 - February 2021 revealed that TB incidence in BC declined by 30.9% and favorable TB outcomes (TB cure or treatment completion) declined by 49.8%. Elucidating differences by migrant status was complicated by the lack of standardized collection of migrant status by the NTP. Qualitative analysis revealed that TB diagnostic and treatment supplies and services became limited and disproportionately accessible across jurisdictions since the pandemic began; however, favorable adaptations were also reported, such as increased telemedicine use and streamlined care referral processes. Participants shared that migrant status is susceptible to misclassification and that TB care is difficult due to the transitory nature of migrants. This study did not identify major differences in TB service delivery or access between migrants and non-migrants in BC; however, migrant status was frequently missing. COVID-19 has overwhelmed health systems worldwide, disrupting timely TB diagnostic and treatment services, and potentially caused underdiagnosis of TB in BC. TB programs in BC should quickly restore essential services that were disrupted by COVID-19 while identifying and preserving beneficial program adaptations, such as telemedicine and streamlined care referral processes. Improved methods for documenting migrant status of TB cases are also needed.